Global Interest in Artificial Intelligence: A Big Data Study - Santonen, Teemu; Kaivo-oja, Jari (Finland, 2025)
This study aims to assess and compare country-specific layman's interest in 17 AI technologies based on Google Trends big data. Government AI Readiness Index 2023 is utilized to evaluate the underlying factors influence on AI technology adoption. As a result, a total of 80 regions showed interest towards AI via Google searches. GDP had a weak correlation to Google trend results. The high-income regions were the most prominent regions (N=40), but the lower-middle-income regions (N=20) overcame the higher-middle-income region (N=16) whereas the low-income group consisted of only two countries. The list of top-ranking regions was somewhat surprising, since many lowerincome regions such as Ethiopia, Pakistan, Sri Lanka and Nepal outperformed higher-income regions. Eleven out of 39 Government AI Readiness Index 2023 indicators had either weak or moderate correlation with Google Trends data.